An Update on Imaging in Idiopathic Intracranial Hypertension - Moreno-Ajona, David; McHugh, James Alexander; Hoffmann, Jan (Frontiers in Neurology, 2020)
Neuroimaging plays an essential role in the diagnostic workup of idiopathic intracranial hypertension with the aims to exclude secondary causes of elevated intracranial pressure and to identify imaging signs that are commonly observed in this disorder. As a valuable expansion of brain imaging, the imaging of the retina using optical coherence tomography has been of increasing value. In particular, this is the case with the latest devices that allow a more accurate distinction between a reduction in retinal nerve fiber layer thickness due to an improvement of papilledema or due to a worsening caused by optic nerve atrophy. Although optical coherence tomography does not yet replace the other elements of the diagnostic workup, it is likely to play an increasing role in diagnosis and follow-up of idiopathic intracranial hypertension. The review focuses on the main findings in neuroimaging, including structural and vascular alterations as well as on the relevance of optical coherence tomography.